Na+/Ca2+ Exchanger 1/2 Double-Heterozygote Knockout Mice Display Increased Nitric Oxide Component and Altered Colonic Motility - Kazuhiro Nishiyama; Yasu-Taka Azuma; Satomi Kita; Naoki Azuma; Satomi Hayashi; Hidemitsu Nakajima; Takahiro Iwamoto; Tadayoshi Takeuchi (Elsevier, 2013)
The Na+/Ca2+ exchanger (NCX) is a plasma membrane transporter involved in regulating intracellular Ca2+ concentrations. NCX is critical for Ca2+ regulation in cardiac muscle, vascular smooth muscle, and nerve fibers. To determine the role of NCX1 and NCX2 in gastrointestinal tissues, we examined electric field stimulation (EFS)-induced responses in the longitudinal smooth muscle of the distal colon in NCX1 and NCX2 double-heterozygote knockout mice (Double HET). We found that the amplitudes of EFS-induced relaxation that persisted during EFS were greater in Double HET than in wild-type mice (WT). Under the non-adrenergic, non-cholinergic (NANC) condition, EFS-induced relaxation in Double HET was similar in amplitude to that of WT. In the experiments in which l-NNA was added under NANC conditions following the EFS, the magnitudes of EFS-induced relaxation were smaller in Double HET than those in WT. In addition, an NCX inhibitor, SN-6, enhanced EFS-induced relaxation but did not affect EFS-induced relaxation under NANC condition, as in Double HET. Moreover, the magnitudes of relaxation induced by NOR-1, which generates NO, were greater in Double HET compared with WT. Similarly, SN-6 potentiated the magnitudes of NOR-1-induced relaxation. In this study, we demonstrate that NCX regulate colonic motility by altering the sensitivity of the inhibitory component. Keywords:: Na+/Ca2+ exchanger, smooth muscle, relaxation, nitric oxide, gastrointestinal motility